Thalassaemia of intermediate severity resulting from the interaction between alpha- and beta-thalassaemia. Issue 6 (December 1978) - Musumeci, S; Schilirò, G; Pizzarelli, G; Fischer, A; Russo, G
Abstract : A Sicilian family is described in which the alpha-thalassaemia gene is interacting in several members with beta-thalassaemia resulting in a balanced alpha/beta chain production ratio. In one patient, affected by homozygous beta-thalassaemia, the presence of alpha-thalassaemia resulted in a less severe clinical expression of the disease, less marked imbalance in the alpha/non-alpha ratio, and a lower level of HbF. Further studies of haemoglobin synthesis are needed to clarify the complex genetic picture that results from the interaction of different forms of thalassaemia.